Bowtie Method: Study of Occupational Health and Safety Risks in Cement Production Process - Ezmeyralda Putri; Mona Lestari; Novrikasari Novrikasari; Desheila Andarini; Anita Camelia; Poppy Fujianti; Titi Nurhaliza (Faculty of Public Health, Hasanuddin University, Makassar, 2021)
The kiln area is an area that has a very complex hazard potential in the cement production process. This study aimed to assess the risks of occupational safety and health during the production process in the kiln area of ​​PT. X uses the bowtie method. This study used a qualitative descriptive design. The informants used were three managers of the clinker production department, one safety manager, and one field operator. Research data were collected through interviews and observations. The data were analyzed qualitatively using the bowtie method. The study results stated that hot dust could be dangerous if it comes out of the system caused by positive pressure, such as the Induced Draft Fan (IDF) turning off, causing losses such as burns to workers. Heat can be dangerous if it experiences a significant increase due to excess fuel, causing losses, such as health-related illnesses. Preventive controls were carried out such as routine inspections. Mitigation controls were carried out such as light signals. Escalation factors can thwart hot dust and heat control, such as the deformation of raw meals. Escalation factor control, such as the implementation of work instructions. PT. X has carried out control in the kiln area, but additional controls are needed.